Gráficos solitons do fluxo da curvatura média. - Sena, Renivaldo Sodré de (2018)
We investigate the existence of graphs that are solitons for the flow of the mean curvature. Under some assumptions, we prove the existence of solitons in warped products I × h M. We also prove a Jenkins-Serrin type result, which gives conditions for the non existence of Dirichlet solution problem for the soliton graph equation. Finally, we study soliton graphs of the mean curvature in the warped product M × h R .